Os efeitos do discurso do professor na construção das identidades dos alunos - Oliveira, Rosymari de Souza (2016)
This research was developed at the Graduate Master's degree program in Teaching of Basic Education of Centro de Ensino e Pesquisa Aplicada a Educacao/ CEPAE from Federal University of Goias, in the research line "theoretical and methodological conceptions and teaching practices." It is the result of an investigation into the teacher's discourse in the school context, and its implications for the construction of students' identities. The research field was one classroom of a public school in Goiania. The subjects of the study were students of the 5th year of elementary school and both portuguese and history teachers. The main goal was to investigate, understand and reveal the effects of teacher's discourse in the way the student dialogically agency language, textual and / or discursive resources , in the work with their own saying, and to observe if it reflects on their identity. Interest was also assess how verbal interactions raised in literacy events indicate the presence of criticality and autonomy of students. Reflecting on the discourses produced in teacher / student's interactions in literacy events, we sought as theoretical support in the socio-interactional character of language studies of Bakhtin (1995) and Fairclough (2001), in the construction of social identities we sougth the theoretical support of Hall (2005) and the studies of literacy Street (2006, 2010, 2014). We also sougth to further investigate the implications of the teaching discourse in identity construction of a more focused and critical subject, who has the ability to expand their view of the world in which it is inserted, reflecting on the different voices with which dialogues, and interact with them in a more conscious and autonomous way. We chose the qualitative research within the interpretative paradigm, and the case study method, supported by interviews, recording and transcription of literacy events and analysis of textual productions of the students. Analyses were carried out in line with the theoretical framework adopted. In order to contribute to an emancipatory educational practice, we develop an educational product in the form of didactic sequence which includes the language as a mediator of identity construction.